Insights into the C–H⋯F–C hydrogen bond by Cambridge Structural Database analyses and computational studies1. Issue 34 (15th April 2015) - Dev, Sagarika; Maheshwari, Sudeep; Roy Choudhury, Angshuman
<x xml:space="preserve">Abstract</x> C–H⋯F–C hydrogen bonding is analysed among fluorinated ethenes using ab initio calculations in the gas phase to understand the nature, strength and directionality of these interactions.